Pleiotropic Benefits of Statins in Cardiovascular Diseases - Wasim, Rufaida; Ansari, Tarique Mahmood; Ahsan, Farogh; Siddiqui, Mohammad Haris; Singh, Aditya; Shariq, Mohammad; Parveen, Saba (Drug Research, 2022)
In 1976, Japanese microbiologist Akira Endo discovered the first statin as a product of the fungus Penicillium citrinum that inhibited the activity of 3-hydroxy-3-methylglutaryl coenzyme A reductase. Their primary mode of action is to lower the blood cholesterol by decreasing hepatic cholesterol production, which upregulates hepatic low-density lipoprotein (LDL) receptors and increases LDL-cholesterol clearance. In addition to cholesterol lowering, statins inhibit other downstream products of the mevalonate pathway, causing the so-called pleiotropic effects. As a result of their pleiotropic effects statins modulate virtually all known processes of atherosclerosis and have beneficial effects outside the cardiovascular system Statins inhibit the post-translational prenylation of small GTP-binding proteins such as Rho, Rac, as well as their downstream effectors such as Rho kinase and nicotinamide adenine dinucleotide phosphate oxidases since they suppress the synthesis of isoprenoid intermediates in the cholesterol biosynthetic pathway altering the expression of endothelial nitric oxide synthase, the stability of atherosclerotic plaques, production of proinflammatory cytokines, reactive oxygen species, platelet reactivity, development of cardiac hypertrophy and fibrosis in cell culture and animal experiments. Inhibition of Rho and Rho-associated coiled-coil containing protein kinase (ROCK), has emerged as the principle mechanisms underlying the pleiotropic effects of statins. However, the relative contributions of statin pleiotropy to clinical outcomes are debatable and difficult to measure because the amount of isoprenoid inhibition by statins corresponds to some extent with the amount of LDL-cholesterol decrease. This article examines some of the existing molecular explanations underlying statin pleiotropy and discusses if they have clinical relevance in cardiovascular diseases.
Keywords: Cardiovascular diseases; Statins; Pleiotropic effect